Spillovers to sectoral equity returns: do liquidity and financial positions matter?. Issue 27 (9th June 2021) - Balli, Faruk; Billah, Mabruk; Balli, Hatice Ozer; De Bruin, Anne
ABSTRACT: In this paper, we investigate spillovers from regional and global equity markets to sectoral equity indices for several different regions/countries. First, we investigate the connectedness of sectoral equity return spillovers and explore the different patterns and magnitudes of spillovers. Next, we look for the determinants of sectoral equity return spillovers. We find the regional and global markets spillovers on sector equity indices are highly dispersed across different markets. Novel to the literature, we examine the liquidity and financial positions of the sectors and find that sector positions are highly influential in explaining the extent of the spillovers. Particularly, our exploration evidence that regional and global spillovers to specific sector equity markets jump significantly when a sector has higher debt and lower interest expense coverage. Similarly, higher profit margins of the sector make it less vulnerable to global and regional shocks. We also find market capitalization of the sectors inversely affects the extent of the spillovers originating from global and regional markets.